2010
DOI: 10.1007/s10551-011-0945-3
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Essence of Stakeholder Relationships: What do we Need in Addition to Power, Legitimacy, and Urgency?

Abstract: Stakeholder relationship, Salience model, Value creation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 30 publications
2
33
0
4
Order By: Relevance
“…More recent empirical research has suggested more stakeholder characteristics, such as trust and learning potential (Myllykangas et al 2010).…”
Section: Prior Literature and Hypotheses Developmentmentioning
confidence: 99%
“…More recent empirical research has suggested more stakeholder characteristics, such as trust and learning potential (Myllykangas et al 2010).…”
Section: Prior Literature and Hypotheses Developmentmentioning
confidence: 99%
“…Stakeholder theory explained the relationship between an organization/company and stakeholders is relational, not a transactional relationship (Myllykangas, Kujala, & Lehtimä ki, 2011).…”
Section: Stakeholder Theorymentioning
confidence: 99%
“…Bundy and colleagues (2013) have moved away from the idea that firms or managers give priority to stakeholders with the most affirmative characteristics (such as power, legitimacy and urgency), a perspective that was suggested by Mitchell and colleagues' seminal theory of stakeholder salience (1997) and examined further in a considerable stream of subsequent research (Agle et al 1999;Eesley and Lenox 2004;Magness 2008;Myllykangas et al 2010;Neville et al 2011;Parent and Deephouse 2007;Tashman and Raelin 2013). Instead, by drawing on the issue management literature (see Dutton and Jackson 1989;Wartick and Mahon 1994), Bundy and colleagues (2013, p. 535) argue that firms or managers respond to specific issues.…”
Section: Theoretical Background: the Strategic Cognition View Of Issumentioning
confidence: 99%